2006
DOI: 10.1162/pres.15.4.381
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Presence and Emotions during Video Game Playing: Does It Matter with Whom You Play?

Abstract: The authors examined whether the nature of the opponent (computer, friend, or stranger) influences spatial presence, emotional responses, and threat and challenge appraisals when playing video games. In a within-subjects design, participants played two different video games against a computer, a friend, and a stranger. In addition to self-report ratings, cardiac interbeat intervals (IBIs) and facial electromyography (EMG) were measured to index physiological arousal and emotional valence. When compared to play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
149
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(171 citation statements)
references
References 18 publications
7
149
2
4
Order By: Relevance
“…For example (in adolescents), EE per minute playing Wii Boxing was 12.1 kJ versus 26.8 kJ for actual spa boxing, and playing Wii Tennis versus actual doubles tennis was 12.5 and .505-512 ACMS = American College of Sports Medicine, AVG = active video game, CP = cerebral palsy, DDR = Dance Dance Revolution, EE = energy expenditure, F = female, HR = heart rate, HR max = maximum heart rate, IDD = individuals with intellectual and developmental disabilities, M = male, MET = metabolic equivalent, PA = physical activity, PS2 = PlayStation2, RER = respiratory exchange ratio, RPE = rating of perceived exertion, SVG = static video game, THBI = total heart beat index, VO 2 = oxygen consumption. 22.2 kJ, respectively [16]. These games are primarily a form of entertainment that may help with motivation (which is important for rehabilitation).…”
Section: Nintendo Wii Versus Actual Sportsmentioning
confidence: 99%
“…For example (in adolescents), EE per minute playing Wii Boxing was 12.1 kJ versus 26.8 kJ for actual spa boxing, and playing Wii Tennis versus actual doubles tennis was 12.5 and .505-512 ACMS = American College of Sports Medicine, AVG = active video game, CP = cerebral palsy, DDR = Dance Dance Revolution, EE = energy expenditure, F = female, HR = heart rate, HR max = maximum heart rate, IDD = individuals with intellectual and developmental disabilities, M = male, MET = metabolic equivalent, PA = physical activity, PS2 = PlayStation2, RER = respiratory exchange ratio, RPE = rating of perceived exertion, SVG = static video game, THBI = total heart beat index, VO 2 = oxygen consumption. 22.2 kJ, respectively [16]. These games are primarily a form of entertainment that may help with motivation (which is important for rehabilitation).…”
Section: Nintendo Wii Versus Actual Sportsmentioning
confidence: 99%
“…De argue that social, physical and media settings have an important impact on the particular experience of playing with others. Some studies have already shown that the specifi c nature of a social context may signifi cantly infl uence players' game experience (Bracken et al, 2005;de Kort et al, 2007;Gajadhar et al, 2008;Lim and Lee, 2009;Ravaja et al, 2006). These fi ndings were linked to the experience of social presence, a concept that stems from CMC literature and is defi ned as 'the sense of being with another' (Biocca et al, 2001).…”
mentioning
confidence: 99%
“…One research implication relates to the empirical methods used to measure emotions. For example, measures of heart rate when playing computer games may increase in response to emotional arousal, but drop in response to greater attentional engagement, both of which are considered indicators of engagement in games [58]. Pairing physiological measures with self-report data, and triangulating between multiple physiological and neurological measures, can help to avoid associated measurement risks.…”
Section: Discussionmentioning
confidence: 99%